2018
DOI: 10.1039/c8cc07746k
|View full text |Cite
|
Sign up to set email alerts
|

From oxide to a new type of molecular tungsten compound: formation of bitetrahedral cluster complexes [{W64-O)23-CCN)4}(CN)16]10− and [{W64-O)23-As)4}(CN)16]10−

Abstract: Two new mixed-valence tungsten cluster anions with bitetrahedral cores, {W6(μ4-O)2(μ3-CCN)4} and {W6(μ4-O)2(μ3-As)4} were synthesized from WO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Examples of the ability of KCN to do this include the formation of unique Re 12 chalcocyanide cluster complexes obtained from ReS 2 and KCN, 32 as well as the original bitetrahedral tungsten cluster complexes that were recently reported. 33 The reactions of ReI 3 with KCN/NaCN and either arsenic or phosphorus that we report here resulted in compounds 1 and 2, which have the quite typical tetrahedral (Re 4 ) clusters for rhenium metal, and they are coordinated by the very unusual (PO 3− or As 3− ) or even unknown (PO 2 3− and AsO 3− ) μ 3 -ligands. Compound 2 was also obtained, when the starting arsenic reagent was As 2 O 3 instead of As.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Examples of the ability of KCN to do this include the formation of unique Re 12 chalcocyanide cluster complexes obtained from ReS 2 and KCN, 32 as well as the original bitetrahedral tungsten cluster complexes that were recently reported. 33 The reactions of ReI 3 with KCN/NaCN and either arsenic or phosphorus that we report here resulted in compounds 1 and 2, which have the quite typical tetrahedral (Re 4 ) clusters for rhenium metal, and they are coordinated by the very unusual (PO 3− or As 3− ) or even unknown (PO 2 3− and AsO 3− ) μ 3 -ligands. Compound 2 was also obtained, when the starting arsenic reagent was As 2 O 3 instead of As.…”
supporting
confidence: 86%
“…In addition, KCN may also stabilize unusual cluster units. Examples of the ability of KCN to do this include the formation of unique Re 12 chalcocyanide cluster complexes obtained from ReS 2 and KCN, as well as the original bitetrahedral tungsten cluster complexes that were recently reported …”
supporting
confidence: 52%
“…However, a handful of structures appear as fused tetrahedra or with intermediate shapes in the way to the octahedron (between 24 and 70% octahedral). Three structures [130][131][132] from different spots of the path are shown in Fig. 25, together with their shape coordinates and some geometrical parameters for comparison.…”
Section: Transition Metal Clustersmentioning
confidence: 99%
“…A characteristic feature of these reactions is their occurrence above the melting points of the corresponding cyanides. We have shown that this approach allows one to obtain compounds with new types of metal cores and/or unusual inner ligands, such as the {W 6 } bitetrahedron with μ 3 -CCN 3– ligands or the {Re 4 } tetrahedron with μ 3 -PO 2 3– and μ 3 -AsO 3– ligands …”
Section: Introductionmentioning
confidence: 99%